(untitled) (Biodiversitas Journal of Biological Diversity, 2018)
Wijayanti DP, Sabdono A, Widyananto PA, Dirgantara D, Hidaka M. 2018. Bacterial symbionts of acroporid corals: Antipathogenic potency against Black Band Disease. Biodiversitas 19: 1236-1242. Black Band Disease (BBD), an infectious coral disease which can cause a rapid decline of coral reefs, has appeared as a serious threat -to many reefs around the world including Karimunjawa National Park, Java Sea. Although it had been studied for more than 30 years, control of disease remains obscure. In the present research coral symbiont bacteria having antipathogenic activity against Black Band bacterial associate were screened and characterized. Fourteen out of 87 bacteria isolates derived from healthy corals showed antagonism against the Black Band bacterial strains. The isolates were then re-examined using disc-diffusion method to confirm the initial observation. The CI6 showed the strongest ability to inhibit BAFBB5, a bacterial strain associated with the BBD. Following the partial sequencings of 16S rDNA, the results indicated that the CI6 isolate was closely related to Virgibacillus salarius strain SA-Vb1, while the BBD associate isolate has strong relation with Virgibacillus marismortui. The results have shown that bacterial strains derived from healthy acroporid corals have potential to be used as a biocontrol agent against BBD.